(untitled) (Global Journal of Science Frontier Research, 2018)
This study details the causes as to how and why Punjab farmers fell into a never -ending cycle of debt which started right from the British Era but became graver with time. Slowly, it turned the state into a graveyard of farmers. The reasons for this poor plight of Punjab farmers are many which can be attributed to the various Governments both at the State and the Center, peasants themselves and to agricultural economists. The loss of resources due to trifurcation of Punjab (1 st November, 1966) , the uncertain political atmosphere during the period of militancy, the absence of democratically elected state government for about a decade (3510 days) and bypassing of primary (agriculture) sector during Economic Liberalization period (initiated in June,1991) made Punjab an ’Orphan’ state. The farmers failed to diversify as no right advice was forthcoming from the economists and continued with wheat and rice combination for which there were no takers of their surplus produce after some years. A Continual increase in the cost of agricultural inputs relative to a minimal increase in the MSP of the crops by the Centre, the pest attacks (whitefly on cotton), depleting underground water level in 80% area and excessive use of fertilizers and pesticides reduced the quality of both the soil and water of the state.